A Stimulator of Entrepreneurial Interest: BCM Entrepreneurship Learning and Training Model - Fauzan Muttaqien; Mokhamad Taufik; Kasno Kasno; Danang Wikan Carito (Mahameru Publisher, 2022)
In the world of school, where learning is organized systematically, the propensity for entrepreneurial curiosity can develop from a young age. According to earlier studies, entrepreneurship interest can be cultivated through the proper educational framework for entrepreneurship studies and efficient entrepreneurship training. This demonstrates how some elements of theoretical research, applied science, and practice must work together. The Business Canvas Model (BCM) entrepreneurship learning model and entrepreneurship training have an impact on the rise of entrepreneurial interest in higher education, according to prior research, which offers empirical support. The study was carried out in the Lumajang Regency's Miftahul Midad Islamic Boarding School. This study set out to determine the level of entrepreneurial interest among the younger generation receiving their education at Islamic boarding schools in the Lumajang district. Multiple linear regression analysis was used to examine the primary data that were received through the distribution of questionnaires. The findings demonstrated that entrepreneurship training and the Business Canvas Methodology (BCM) learning model had an impact on participants' interest in entrepreneurship. A suitable and systematic methodology is required to encourage students to become competent entrepreneurs given the significant influence that education and entrepreneurship training have on their interest in entrepreneurship.